An overview of chiral separations of pharmaceutically active substances by HPLC (2018–2020) - Grybinik, Sofiya; Bosakova, Zuzana (Monatshefte für Chemie, 2021)
This review provides a brief survey of chiral separation of pharmaceutically active substances published over the last 3 years (2018–2020). Chiral separation of drugs is an important area of research. The control of enantiomeric purity and determination of individual enantiomeric drug molecules is a necessity especially for clinical, analytical, and regulatory purposes. Among chromatographic resolution methods, high-performance liquid chromatography based on chiral stationary phases remains the most popular and effective method used for chiral separation of various drugs. In this review, attention is paid to several classes of chiral stationary phases that have been the most frequently used for drug enantioseparation during this period. Graphic abstract